Status Hukum Mou Antara Ri Dengan Gam Dalam Hukum Internasional Dan Nasional - Muhammad Ihsan (Syarah: Jurnal Hukum Islam & Ekonomi, 2019)
The agreement between the government of Indonesia and GAM socalled MoU Helsinki last one decade, but when it was signed inHelsinki at Agust fifteenth, 2005, that was questioned by peopleabout the statue, in Vienna Convention on the law of treaties 1969,the treaty making by the states parties, but the statue of GAM are notdistinct on international law. The statue of MoU, could be answer ofGAM statue. Beside, many points in MoU that indicate about selfgoverment,in the system of government of Indonesia, practicesspecial autonomy or regional autonomy. MoU becomes a problem inconstitutional law of Indonesia. because of MoU is like a constitutionand the source of law for Aceh. Based on the explanation, thisresearch will analyze of statue of MoU Helsinki between thegovernment of Indonesia and the Free Aceh Movement oninternasional and national law. This research use the normatif lawresearch by conceptual approach and statute approach. MoU Helsinkias inspired source’s of Aceh’s government because of Aceh is thespecial region